Informing a Nation Horace Greeley - Allen, Edward (Ency. Britannica Chicago, 1962)
Horace Greeley believed in the destiny of the United States, and that belief became the guiding spirit of the New York Tribune. It became the largest and most powerful newspaper in the nation in the second half of the 19th century. Greeley became a familiar figure to every American of his time and the greatest editor in the United States journalism.
Keywords: Greeley, Horace -- 1811-1872; United States Politics and government -- 1849-1877